Understanding the impact of promoting da’wah using social media platforms among Pakistani Muslims - Keerio, Imran Khan; Luhana, Kirshan Kumar; Shah, Asadullah (GCLT (Global Center for Legal Thought), 2023)
Social media is a term used to describe websites and applications that allow users to create and share content or participate in social networking. Examples of popular social media sites and applications include Facebook, Instagram, Twitter, LinkedIn, Snapchat, and YouTube. Social media can be a powerful tool for Dawah or Islamic outreach. It can spread awareness about Islam, share Islamic teachings, and connect with people of different backgrounds and beliefs. Social media can also be used to engage. The sole purpose of this study is to find out how Islamic content can be promoted over social media in Pakistan, in other words, how Da’wah can be promoted over social media. Social Media platforms are widely used around the globe by Pakistani people, especially the youth of Pakistan, who spend most of their time on social media, so consider social media as a tool for how Da’wah content can be promoted in Pakistan. The methodology selected for this study is a quantitative approach using a survey questionnaire instrument. Data were collected from young youth of Pakistani students. The data indicates how Pakistani people use social media and what medium they like most. So, da’wah content can be converted to such content to maximize its social media promotion. It will help the buildup of a society based on Islamic principles.